فعالية برنامج علاجي لتخفيف مستوى صعوبات تعلم الكتابة دراسة ميدانية بابتدائية بوقنفودة العلمي بالأغواط - امينة نجام; لبصير سفيان (My University, 2023)
The current study aimed to determine the effectiveness of a remedial program in alleviating writing difficulties among a sample of students with writing difficulties. The sample size was 16 students. The study was applied to them at the Bouqanfouda Scientific Primary School in Laghouat, which was conducted during the month of May of the year 2023. After pre-measurements on the control and experimental groups in both the level of writing difficulties and the level of handwriting, then applying the therapeutic program, and then carrying out post-measurements of the differences between the control and experimental groups, in both the level of writing difficulties and the handwriting level, the study yielded results. next: There are statistically significant differences between the experimental and control groups in the level of writing difficulties among a sample of primary school students in favor of the control group. There are statistically significant differences between the experimental and control groups in the level of handwriting among a sample of primary school students in favor of the experimental group